SECTORAL BANK CREDIT AND ECONOMIC DEVELOPMENT: EVIDENCE FROM NIGERIA (American Journal of Business Management, Economics and Banking, 2024)
The debate on the issue of sectoral bank credit and economic development has over the years drawn attention of academicians and policy makers across nations with varying opinion motivated our interest in re-examining the link between sectoral bank credit and economic development in Nigeria from 1986 to 2021 using the Autoregressive Distributive Lag (ARDL) along with its associated long run bond test and the Granger causality test as estimation techniques. Bank credit to Agricultural Sector (SCAS), Manufacturing Sector (SCMS), Mining and Quarrying Sector (SCMQ) and General Commerce and Trade (SCTG) were the sectors considered while Per Capita Income (PCI) proxied economic development. Pre-estimation was done with the aid of unit root test which showed fractional integration order necessitating the need for the use of ARDL as stated earlier and further finds revealed absence of long run equilibrium association among sectoral bank credit and economic development while insignificant negative link was observed between sectoral bank credit to agriculture and trade and general commerce and positive insignificant link between sectoral bank credit to manufacturing sector and mining and quarrying sector. The causality result showed absence of causality among agricultural and manufacturing sectors with economic development, unidirectional causality between mining and quarrying economic development and bidirectional causality with between trade and general commerce and economic development. The study recommends the need for proper awareness on the important of agricultural sector and trade and general commerce role in the development of the economy and as such the need for more credit to be directed to those sectors and that proper policy measures be put in place to ensure that credits given to these sectors are not diverted for use in other areas.